Pengaruh Model CTL Berbantuan Buklet Terhadap Kemampuan Berpikir Kreatif Siswa Kelas IV Sekolah Dasar - Shinta Dewi; Murtono Murtono; Ratri rahayu (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to analyze the effect of Contextual Teaching and Learning (CTL) model assisted by booklets on the students’ creative thinking ability at grade IV elementary school. The choice of booklet media CTL model was considered appropriate for SDA and poetry materials on the theme of Cita-Citaku. Students could relate the materials to their life environment through CTL model and booklet media; this can be done in groups or individually. This study was quantitative experimental research with nonequivalent posttest-only control group design. The samples in this study were fourth grade students of SDN 1 Bulungcangkring as the experimental class and fourth grade students of SDN 3 Bulungcangkring as the control class. Based on the results of the study, it was revealed that (1) the thinking ability of students taught with CTL model assisted by booklet was better than those taught by the lecture model; (2) the average creative thinking ability of students taught with the CTL learning model was more than 70 (KKM). It could be concluded that there was an effect of Contextual Teaching and Learning model assisted by booklets on the students’ creative thinking abilities at grade IV elementary school.